The incidence of work-related low back pain among currently practicing physiotherapists in Bloemfontein - R. Barnes; J. Birch; M. M. Cloete; L. Joubert; A. C. Usher; M. M. Nel (AOSIS, 2007)
Physiotherapy practice involves the performance of strenuous physical activities related to the delivery of patient rehabilitation.  No evidence of studies relating to physiotherapy work-related low back pain (WRLBP) in South Africa could be found.  The aims of this study were to retrospectively investigate the incidence of work related low back pain among currently practicing physiotherapists in Bloemfontein, to determine the contributing risk factors, and to determine the responses of the physiotherapists to injury. Eighty four physiotherapists participated in this descriptive study. The results indicated that 67% of respondents had experienced work related low back pain and the 95% confidence interval for the incidence of WRLBP among physiotherapists in Bloemfontein is [56.8%; 76.6%].  Therapists performing cardio-thoracic related tasks had the most significant confidence interval of WRLBP [2.2%; 35.1%]. Fifty eight percent of respondents who had WRLBP reported that their symptoms were exacerbated by clinical practice.  The results of the study suggest that it is the nature of the job design which predisposes physiotherapists to injury and not a lack of kinetic handling knowledge. Further research is needed to develop methods to reduce the risks of WRLBP which are inherently part of physio- therapy practice.